A review of emotional and sexual abuse of elite child athletes by their coaches. Issue 1 (2nd January 2021) - Wilinsky, Charlotte L.; McCabe, Allyssa
ABSTRACT: Emotional abuse and sexual abuse are often co-occurring forms of child maltreatment that can have numerous negative effects on development. This narrative review synthesises research on emotional and sexual abuse of elite child athletes by their coaches to examine the dynamics and consequences of abuse in the elite sport context and to investigate characteristics of this context – in which the coach-athlete relationship is central – that make these athletes especially vulnerable to abuse. This paper contributes to the literature through using a developmental perspective to identify these characteristics, which are the intensity and one-dimensionality of child athletes' experiences at the elite level. These characteristics are dangerous because they lead to the normalisation of the abuse and isolation of the still-developing athlete. Critical issues related to both emotional and sexual abuse of elite child athletes are also discussed, including internalisation and rationalisation of the abuse, disruption of identity, and dynamics surrounding disclosure.